A novel AIE fluorescent probe for the monitoring of aluminum ions in living cells and zebrafish. Issue 12 (27th May 2022) - Gan, Yabing; Yin, Guoxing; Wang, Jianhua; Yin, Peng
Abstract : A novel AIE fluorescent probe BTD was developed for the monitoring of Al 3+, along with high sensitivity and high selectivity. This probe was successfully applied to the sensing of Al 3+ in living cells and zebrafish. Abstract : A novel fluorescent probe BTD with aggregation induced emission (AIE) characteristics for the monitoring of Al 3+ was developed. This fluorescent probe could be used to detect Al 3+ in aqueous solution under mild conditions, along with high sensitivity and high selectivity. The detection limit of the probe BTD for Al 3+ is as low as 3.25 nM, which is below the WHO recommendation concentration (7.41 μM) for drinking water. Furthermore, this probe was successfully applied to the sensing of Al 3+ in living cells and zebrafish.